Komisaris Independen dalam Memoderasi Kepemilikan Institusional Terhadap Penjualan Pihak Berelasi - Ermad M.J; Zulkifli Umar; Dhea Adhima Suemdra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to examine the role of independent commissioners in moderating the effect of institutional ownership on sales to related parties. This research is a sample study, which includes 207 companies from 510 manufacturing sector companies during the 2017-2019 observation year. The sample was selected with certain criteria techniques. The analytical method used is moderated regression analysis. The results of the study found that institutional ownership had no significant effect on sales to related parties. The independent commissioner moderated the homologizer moderated the influence of institutional ownership on sales to related parties.